2015
DOI: 10.56059/jl4d.v2i2.105
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance in Asian Open and Distance Learning: Policies and Implementation

Abstract: Open universities have emerged as an innovative pillar in the expansion of access to higher education participation, with single-mode distance education providers broadening access in many countries through economies of scale supported by large enrolments. These models raise questions about the quality of education provided. This paper reports on a comparative case study of quality assurance (QA) programs in distance education at three open universities in Southeast Asia. Focusing on QA development and impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…While there are a large number of studies (Hoecht, 2006;Ryan, 2015;Kahveci et al, 2012) that have focused on the practices of QA in the traditional education system, some studies have looked into the same from ODL (Perraton, 2012;Darojat et al, 2015;Kihwelo, 2013;Scull et al, 2011;Stella and Gnanam, 2004). However, while some studies have concentrated on the nature and importance of ODL, some other studies (Darojat et al, 2015;Kihwelo, 2013;Scull et al, 2011;Stella and Gnanam, 2004) have shown the use of QA in the context of ODL. In this respect, while previous studies (Stella and Gnanam, 2004) are mostly based on developed countries, only a few studies (Darojat et al, 2015;Belawati and Zuhairi, 2007) have examined the use of QA in ODL from a developing country's perspective.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…While there are a large number of studies (Hoecht, 2006;Ryan, 2015;Kahveci et al, 2012) that have focused on the practices of QA in the traditional education system, some studies have looked into the same from ODL (Perraton, 2012;Darojat et al, 2015;Kihwelo, 2013;Scull et al, 2011;Stella and Gnanam, 2004). However, while some studies have concentrated on the nature and importance of ODL, some other studies (Darojat et al, 2015;Kihwelo, 2013;Scull et al, 2011;Stella and Gnanam, 2004) have shown the use of QA in the context of ODL. In this respect, while previous studies (Stella and Gnanam, 2004) are mostly based on developed countries, only a few studies (Darojat et al, 2015;Belawati and Zuhairi, 2007) have examined the use of QA in ODL from a developing country's perspective.…”
Section: Introductionmentioning
confidence: 99%
“…However, while some studies have concentrated on the nature and importance of ODL, some other studies (Darojat et al, 2015;Kihwelo, 2013;Scull et al, 2011;Stella and Gnanam, 2004) have shown the use of QA in the context of ODL. In this respect, while previous studies (Stella and Gnanam, 2004) are mostly based on developed countries, only a few studies (Darojat et al, 2015;Belawati and Zuhairi, 2007) have examined the use of QA in ODL from a developing country's perspective. Available evidence indicates that the acceptance of ODL differs from country to country.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations